Factor affecting housing price in Malysia / Nurul Su’aidah Abd Karim - Abd Karim, Nurul Su’aidah (2015)
This paper aim is to analyze the factors that influencing the housing price in Malaysia. The determinants are being measure in order to know whether it affect the housing price volatility. The housing appreciation is depending on a specific location, either in big or smaller towns. The dependent variable in this research is housing price index (HPI) and the independent variables to be used in this research are macroeconomic factor which are Lending interest rate (LIR), gross domestic product (GNI), Inflation rate (IR) and Unemployment rate (UR). The study is an attempt to investigate and examine the housing price volatility in Malaysia over 2006-2013 by using the quarterly basis of time series of the variables will be collected from the Thomson one banker website. Multiple regression analysis will be used in order to reveal about the relationship between the dependent and the independent variables that has been chosen. The result of this thesis would provide us with the indicate view and the macroeconomic factors that can affect the housing price in Malaysia. The result from this study has provided valuable point of view for answers to the problem statement and hypothesis statements of this project paper. Using the basis of 5% significance level, can be concluded that only gross national income (GNI) and unemployment rate (UR) plays a significant relationship with housing price index (HPI). Whereas, the other selected macroeconomics lending interest rate (LIR) and inflation rate (IR) do not appear to have any significant relationship with housing price. The results of the study also showed that 78.36% of housing price was explained by four selected macroeconomic variables. Therefore, more research needs to be done in order to identify more variable and factors or determinants that account for the reminder 21.64%. This is important for housing investor, house buyer and the policy maker on their decision-making process.